Biogeochemistry of high altitude soils on ophiolites in the Western Italian Alps - Michele D'Amico; Franco Previtali (2009)
Soils on ophiolitic materials are usually rich in Mg, Fe and heavy metals, with a pH value close to neutrality and a high base status. The low Ca/Mg ratio and the high metal content can cause toxicity symptoms on biological communities. Thus, plant associations are often peculiar and rich in adapted species. Chemical and biological properties of alpine and arctic soils formed on these materials have seldom been studied worldwide. 97 soil profiles (associated with phytosociological surveys) were opened and analyzed above the treeline in Mont Avic Natural Park (Val d’Aosta, north-western Italy), 27 of which in heavily cryoturbated or snowbed habitats (above 2550 m above sea level). The aim was to verify the active pedogenic processes, the mobility and bioavailability of heavy metals, to recognize the edaphic properties influencing plant distribution and possible toxic effects on microbial and arthropodal communities. The climate is intra-alpine (average temperatures between 2 and -3°C, average rainfall below 1300 mm/y); water scarcity is never a limiting factor for vegetation. The substrate is composed of ophiolitic rocks, with serpentinite as the most common rock type and minor gabbros, amphibolites and calcschists. Soils are usually acidic on all substrates, with pH values increasing from stable, low altitude sites to heavily cryoturbated and eroded ones. Substrate influences the particle size distribution (fine on serpentinite), the Ca/Mg ratio (often lower on ultramafic materials) and heavy metal content. Pedo-geomorphic processes (cryoturbation and freeze-thaw cycles-induced erosion and deposition) “rejuvenate” soils by adding non-weathered material on the top of the profile: this phenomena differentiate the edaphic properties on the different substrates and increase the metal concentration in biologically active horizons on serpentinite. The low pH values and the waterlogging at snowmelt cause the release of the metals from the primary minerals, thus increasing the mobile and bioavailable contents: for ...